ON THE PLACEMENT OF APRON DOSEMETERS AND DOSE ASSESSMENT IN INTERVENTIONAL CARDIOLOGY PROCEDURES: PRELIMINARY RESULTS. Issue 19 (24th September 2022) - Ferrari, P; Becker, F; Campani, L; Jansen, J; Jovanović, Z; Krstić, D; Mariotti, F; Teles, P; Venturi, G
Abstract: Personnel involved in interventional practices are likely to be exposed to higher radiation doses than other workers in the medical field. Personnel monitoring and radiation protection measures play a crucial role in keeping these doses below the limits. EURADOS (European Radiation Dosimetry Group) Working Group 12 performed a series of investigations showing how the complexity of the scattered field reaching the operators can influence the doses to the operators. The present work was aimed at determining the possible effects on the registered doses of the scattered field and the actual position of a dosemeter on apron. This study has been performed through Monte Carlo simulations and it was validated through measurements. It does not claim to identify the 'best' position for the dosemeter, but to assess the variability of its response, showing how a variability of the order of +/− 30% to 40 should be taken into account.